HOW TO FRAME EDIBLE ART - Andrzejewski, Adam (The Nordic Journal of Aesthetics, 2018)
The question of whether food is art depends primarily on the definition of art that we agree to accept. The article proposes a model that helps us to focus our mind on what could be, and how we should understand the art of food, if we accept, having applied a fairly liberal theory of art, that food can actually be art. It is argued that there are no methodological or factual constraints indicating that food could not, under some circumstances, be high art. This hypothetical form of art is called ‘edible art’.